Distribution of Carbonic Anhydrase in the Uterus of Late-Term Pregnant Spiny Dogfish (Squalus Acanthias) - FLÜGEL, CASSANDRA; LÜTJEN-DRECOLL, ELKE (Company of Biologists, 1991)
Carbonic anhydrase (CA) activity was localized in the late-term pregnant spiny dogfish uterus using the modified histochemical staining method of Hansson. Staining was found in the cytoplasm of red blood cells and in the membranes of the endometrial epithelial cells. Under the electron microscope, reaction products were seen in the basolateral membranes of the superficial cells, whereas the apical membranes were unstained. The cells of the underlying layer contacting the stromal capillaries showed staining in all their membranes. This staining pattern is similar to that found in other epithelia noted for active ion transport.